Modality and identity construction in the narratives of Libyan EFL learners / Hanan Bulgasim Salem Buhassan - Buhassan, Hanan Bulgasim Salem (2013)

(untitled)
Identity construction occurs either in the personal or social levels. Such construction of identity manifests in various ways most particularly through the narratives. Therefore this study seeks to examine the identity construction of Libyan ELF learners through their personal narratives. More specifically, this study focuses on identity construction through the use of mood and modality. Thirty personal narratives from thirty Libyan EFL learners are examined and analyzed. The study uses the qualitative research paradigm in collecting and analyzing the data. Positioning theory is used as the theoretical framework (Bamberg 1997, 2003, 2004, 2010 and 2011). The researcher also adopted the theories introduced by Halliday in Halliday & Hasan (1989) and Halliday & Matthiessen (2004). The findings of the study reveal that academic identity, personal identity, ethnic identity, social identity, national identity are the identities that Libyan EFL learners construct. Furthermore, the imperative, declarative, and interrogative modals are the moods in which identity construction is revealed. It is also evident that modalities enhance the identity constructed by the Libyan EFL learners. It can be generalized that construction of identity through narrative discourses is guided by social ideology and linguistic choices.